Career guidance and counselling in times of volatile labour markets and dynamic biographies: announcement: Doctoral Summer School in Mannheim, Germany, September 4 - 9, 2017 - Weber, Peter; Katsarov, Johannes W. (Newsletter, 2017)
Announcement: Doctoral Summer School in Mannheim, Germany, September 4 - 9, 2017